(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article analyzes current trends and prospects for the development of the restaurant business in Russia in the context of globalization and technological progress. The key success factors of restaurant enterprises are considered, such as high-quality products and services, innovation, effective marketing strategies and adaptation to consumer preferences. Special attention is paid to digitalization, environmental friendliness, personalization of the offer, development of the "Dark Kitchen" concept and gastronomic tourism.